2011
DOI: 10.1088/0004-637x/735/1/63
|View full text |Cite
|
Sign up to set email alerts
|

THE SUPER-LINEAR SLOPE OF THE SPATIALLY RESOLVED STAR FORMATION LAW IN NGC 3521 AND NGC 5194 (M51a)

Abstract: We have conducted interferometric observations with the Combined Array for Research in Millimeter Astronomy (CARMA) and an on-the-fly mapping with the 45 m telescope at Nobeyama Radio Observatory (NRO45) in the CO (J = 1-0) emission line of the nearby spiral galaxy NGC 3521. Using the new combined CARMA + NRO45 data of NGC 3521, together with similar data for NGC 5194 (M51a) and archival SINGS Hα, 24 μm THINGS H i, and Galaxy Evolution Explorer/Far-UV (FUV) data for these two galaxies, we investigate the empir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
204
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(242 citation statements)
references
References 75 publications
(125 reference statements)
35
204
2
1
Order By: Relevance
“…For example, Liu et al (2011) argue that when one subtracts the diffuse component from SFR maps, then a super-linear resolved KS relation emerges in NGC 3251 and NGC 5194. On the other hand, Blanc et al (2009);Shetty et al (2013a,b) suggest that due to issues related to bisector fitting methods (which have been used in many of the resolved KS relation studies), the true KS slope should be sub-linear.…”
Section: Star Formation Laws and Efficienciesmentioning
confidence: 99%
“…For example, Liu et al (2011) argue that when one subtracts the diffuse component from SFR maps, then a super-linear resolved KS relation emerges in NGC 3251 and NGC 5194. On the other hand, Blanc et al (2009);Shetty et al (2013a,b) suggest that due to issues related to bisector fitting methods (which have been used in many of the resolved KS relation studies), the true KS slope should be sub-linear.…”
Section: Star Formation Laws and Efficienciesmentioning
confidence: 99%
“…Other studies using 12 CO(2−1) also show a linear correlation (e.g., Leroy et al 2008;Schruba et al 2011), including one that combined single-dish 12 CO(2−1) data with interferometric 12 CO(1−0) data (Rahman et al 2011). These 12 CO(2−1) studies analyzed a substantial number of nearby galaxies, though it should be recognized that some studies based on 12 CO(1−0) data showed a superlinear (power-law) correlation, rather than a linear correlation (e.g., Wong & Blitz 2002;Kennicutt et al 2007;Liu et al 2011). This suggests that the choice of the CO transition for deriving Σ H 2 could affect N fit values (see Bigiel et al 2008).…”
Section: The K-s Relation Index: Resolution Vs 12 Co Transitionsmentioning
confidence: 99%
“…Spatially resolved K-S relation studies published in the past decade (e.g., Kennicutt et al 2007;Bigiel et al 2008Bigiel et al , 2010Bigiel et al , 2011Leroy et al 2008;Blanc et al 2009;Eales et al 2010;Verley et al 2010;Liu et al 2011;Rahman et al 2011Rahman et al , 2012Schruba et al 2011;Ford et al 2013;Viaene et al 2014) found a wide spread in the value of the power relation index (N ≈ 0.6−3) both within and among galaxies. For a comprehensive review of the most recent SF relation studies on sub-kpc scales, we refer to Kennicutt & Evans (2012).…”
Section: Introductionmentioning
confidence: 99%
“…The same background was subtracted for all apertures. Recent studies of nearby galaxies have shown the importance of background subtraction to derive the star-formation laws (Blanc et al 2009;Rahman et al 2011;Liu et al 2011). However, this is most important for regions in galaxies forming stars at a low rate that can be resolved only in nearby galaxies.…”
Section: Himentioning
confidence: 99%
“…Whether and how this law varies is subject of an on-going debate in the literature (Kennicutt 1998b;Gao & Solomon 2004;Kennicutt et al 2007;Leroy et al 2008;Bigiel et al 2008;Blanc et al 2009;Rahman et al 2011;Liu et al 2011). Deviations between quiescent starforming galaxies and interacting systems can have important implications regarding our understanding of galaxy formation and evolution.…”
Section: Schmidt-kennicutt Lawmentioning
confidence: 99%